Relasi Kuasa antara Kepala Sekolah dan Guru: Kajian Teoretis terhadap Implementasi Kebijakan Pendidikan Berbasis Kinerja - Muhammad Farras Abiyyu; Isa Anshori (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to theoretically examine the power relations between school principals and teachers within the framework of implementing performance-based education policies. A qualitative approach was adopted, with a literature review serving as the primary research method. Power relations in educational institutions are inherently shaped by the hierarchical structure of school organizations, where principals hold decision-making authority while teachers act as policy implementers. Drawing on key sociological theories of education, such as Pierre Bourdieu’s theory of social reproduction and Michel Foucault’s concept of power relations, the study reveals that performance-based education policies tend to reinforce unequal power structures. Teachers are frequently positioned as passive recipients of top-down policies, with little involvement in the decision-making process. This lack of participation has significant implications, particularly in diminishing teachers’ professional autonomy in classroom practices. Consequently, the study recommends adopting more democratic and participatory policy-making approaches in schools to promote more balanced and equitable working relationships between principals and teachers. Such an approach is expected to improve not only school governance but also the overall effectiveness of educational outcomes.